Adverse pregnancy outcomes in an area where multidrug-resistant plasmodium vivax and Plasmodium falciparum infections are endemic. - Poespoprodjo, JR; Fobia, W; Kenangalem, E; Lampah, D; Warikar, N; Seal, A; Mcgready, R; Sugiarto, P; Tjitra, E; Anstey, N; Price, R (2008)
BACKGROUND: Plasmodium falciparum infection exerts a considerable burden on pregnant women, but less is known about the adverse consequences of Plasmodium vivax infection. METHODS: In Papua, Indonesia, where multiple drug resistance to both species has emerged, we conducted a cross-sectional hospital-based study to quantify the risks and consequences of maternal malaria. RESULTS: From April 2004 through December 2006, 3046 pregnant women were enrolled in the study. The prevalence of parasitemia at delivery was 16.8% (432 of 2570 women had infections), with 152 (35.2%) of these 432 infections being associated with fever. The majority of infections were attributable to P. falciparum (250 [57.9%]); 146 (33.8%) of the infections were attributable to P. vivax, and 36 (8.3%) were coinfections with both species. At delivery, P. falciparum infection was associated with severe anemia (hemoglobin concentration, <7 g/dL; odds ratio [OR], 2.8; 95% confidence interval [95% CI], 2.0-4.0) and a 192 g (95% CI, 119-265) reduction in mean birth weight (P<.001). P. vivax infection was associated with an increased risk of moderate anemia (hemoglobin concentration, 7-11 g/dL; OR, 1.8; 95% CI, 1.2-2.9; P=.01) and a 108 g (95% CI, 17.5-199) reduction in mean birth weight (P<.019). Parasitemia was associated with preterm delivery (OR, 1.5; 95% CI, 1.1-2.0; P=.02) and stillbirth (OR, 2.3; 95% CI, 1.3-4.1; P=.007) but was not associated with these outcomes after controlling for the presence of fever and severe anemia, suggesting that malaria increases the risk of preterm delivery and stillbirth through fever and contribution to severe anemia rather than through parasitemia per se. CONCLUSIONS: These observations highlight the need for novel, safe, and effective treatment and prevention strategies against both multidrug-resistant P. falciparum and multidrug-resistant P. vivax infections in pregnant women in areas of mixed endemicity.